Management of Polypharmacy and Potential Drug–Drug Interactions in Patients with Pulmonary Aspergillosis: A 2-Year Study of a Multidisciplinary Outpatient Clinic - Dario Cattaneo; Alessandro Torre; Marco Schiuma; Aurora Civati; Giacomo Casalini; Andrea Gori; Spinello Antinori; Cristina Gervasoni (Journal of Fungi, 2024)
Pulmonary aspergillosis mainly affects elderly patients, patients with pulmonary complications, patients with hematological malignancies, organ transplant recipients, or critically ill patients. Co-morbidities may result in a high rate of polypharmacy and a high risk of potential drug–drug interaction (pDDI)-related antifungal azoles, which are perpetrators of several pharmacokinetic- and pharmacodynamic-driven pDDIs. Here, we report the results of the first 2-year study of an outpatient clinic focusing on the management of therapies in patients with pulmonary aspergillosis. All patients who underwent an outpatient visit from May 2021 to May 2023 were included in this retrospective analysis. A total of 34 patients who were given an azole as an antifungal treatment (53% voriconazole, 41% isavuconazole, and 6% itraconazole) were included. Overall, 172 pDDIs were identified and classified as red- (8%), orange- (74%), or yellow-flag (18%) combinations. We suggested handling polypharmacy in those patients using specific diagnostic and pharmacologic interventions. As expected, red-flag pDDIs involved mainly voriconazole as a perpetrator (71%). However, nearly 30% of red-flag pDDIs were not related to antifungal therapy. These findings highlight the importance of conducting an overall assessment of the pharmacologic burden and the key role played by a multidisciplinary team for the optimization of therapies in patients with pulmonary aspergillosis.